Setting up a surveillance system for sexually transmitted diseases in the general population with prospective data collection from private-practice and public-practice doctors in Hong Kong - Tsui Hi; Lau Man; Ho King; Lin Chunqing; Lau Joseph TF; Gu Jing; Lo Kuen (BMC, 2011)
Abstract Background Existing surveillance systems for sexually transmitted diseases (STD) and reproductive tract infections (RTI) are important but often ineffective, as they tend to omit cases diagnosed by private-practice doctors Methods During a 15-day study period, 277 private-practice doctors and all public-practice doctors of all the eight local Social Hygiene Clinics (SHC) in Hong Kong filled out daily a standard log-form, recording the number of patients diagnosed with particular types of STD/RTI. Projections for all local private-practice and public-practice doctors were made by the stratification method. Results Data showed that 0.75% of private patients and 40.92% of public patients presented the listed STD/RTI syndromes. It is projected that 12,504 adults were diagnosed with such syndromes by all local private-practice (10,204) or public-practice doctors (2,300); 0.22% (male: 0.26%; female: 0.18%) of the local adult population would fall into this category. The ratio of STD/RTI cases, diagnosed by private-practice versus public-practice doctors, was 4:1. Of the participating private-practice doctors, 96% found the process easy to administer and 75% believed that it was feasible for such a STD/RTI surveillance system to be implemented annually. Conclusions Surveillance of STD/RTI based only on data obtained from the public health system is inadequate. Data obtained from public-practice and private-practice doctors are very different and the majority of the patients presented their STD/RTI syndromes to private-practice doctors. The proposed, improved surveillance system is feasible and has the strengths of involving both private-practice and public-practice medical practitioners and being well accepted by private-practice doctors.